2004
DOI: 10.1080/13854040490888530
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences in Wechsler Intelligence Scale for Children—Third Edition (WISC-III) Profiles: Support for Subtest Analysis in Clinical Referrals

Abstract: Our study supports the reliability and validity of profile analysis in children with neurobiological disorders. Three mutually exclusive WISC-III profiles were identified that characterized the majority of children with autism (low coding or Freedom from Distractibility Index with low Comprehension), attention deficit hyperactivity disorder and learning disability (low Coding or FDI without low comprehension), and brain injury (low Performance without low Coding or FDI). The profiles suggest attention, writing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 71 publications
9
66
0
2
Order By: Relevance
“…One hypothesis that may explain this correlation is that an earlier start to epilepsy could coincide with the period in which certain abilities are starting to be acquired 16 . One factor affecting the finding of a correlation between age for the first seizure and performance IQ, but not with verbal IQ, could be the fact that the verbal tasks making up the verbal IQ use material that is learnt and highly consolidated, which is less vulnerable to brain alterations, whilst the non-verbal tasks used in the performance IQ use material that demands strategy formulation to emit an adequate response 27 .…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis that may explain this correlation is that an earlier start to epilepsy could coincide with the period in which certain abilities are starting to be acquired 16 . One factor affecting the finding of a correlation between age for the first seizure and performance IQ, but not with verbal IQ, could be the fact that the verbal tasks making up the verbal IQ use material that is learnt and highly consolidated, which is less vulnerable to brain alterations, whilst the non-verbal tasks used in the performance IQ use material that demands strategy formulation to emit an adequate response 27 .…”
Section: Discussionmentioning
confidence: 99%
“…This assessment of cognitive ability consists of 13 subtests, 10 of which are used to calculate a standardized fullscale IQ score. Based on previous studies discriminating individuals with ADHD from control subjects using Wechsler scales (Antshel et al 2007;Ek et al 2007;Filippatou & Livaniou 2005;Mayes & Calhoun 2004;Pineda et al 1999), we investigated performance on six measures by genotype: information, coding, block design, freedom from distractibility (derived from scores on the arithmetic and digit span subtests), picture completion and comprehension. We also examined performance on two general measures of cognition (performance IQ and verbal IQ) by genotype.…”
Section: Symptomatology and Cognitive Analysis In Adhd Subjectsmentioning
confidence: 99%
“…We considered a combination score of Յ2/Ն3 to be the best to predict non-PDD/PDD. 8 indicate that clinicians should not rely heavily on the cognitive profile when diagnosing PDD. Nevertheless, because the four subtests are easy to administer and the calculating formula of the combination score is very simple, careful interpretation of the score could provide additional information on PDD to clinicians.…”
Section: Resultsmentioning
confidence: 99%
“…Mayes and Calhoun classified each child's WISC-III profile type by ranking the index and the subtest scores from lowest to highest, and found that low Coding with low Comprehension or low Freedom from Distractibility index with low Comprehension profile correctly identified 56% of children with high-functioning (IQ Ն 80) autism and 76% without autism. 8 Compared to reviewing all of the subtests and analyzing them as in the aforementioned study, it may be more useful in clinical settings to use a simple parameter for the selected subtests. In the present study we propose an original combination score from the Japanese version of the WISC-III 9 and examine its utility for predicting PDD in children.…”
mentioning
confidence: 99%